WISC‐V Profiles and Their Correlates in Children with Autism Spectrum Disorder without Intellectual Developmental Disorder: Report from the ELENA Cohort. Issue 5 (27th November 2020) - Audras‐Torrent, Lee; Miniarikova, Ela; Couty, Flore; Dellapiazza, Florine; Berard, Mathilde; Michelon, Cécile; Picot, Marie‐Christine; Baghdadli, Amaria
Abstract : The intellectual functioning of people with autism spectrum disorder (ASD) without intellectual developmental disorder (IDD) has not been widely studied. However, marked heterogeneity in assessment measures, samples, and results has been an obstacle for the generalization of findings. We aimed to (a) describe WISC‐V intellectual functioning in a sample of children with autism spectrum disorder without intellectual developmental disorder, (b) identify WISC‐V profiles, and (c) explore whether WISC‐V intellectual functioning is related to ASD symptom severity and adaptive skills. Our sample consisted of 121 children from 6 to 16 years of age with ascertained ASD without an intellectual developmental disorder (IDD). The intellectual functioning of the participants was within the average range. Intra‐individual analysis showed that children with ASD performed better on visual than auditory working‐memory tasks. Moreover, the intellectual functioning of the participants correlated negatively with ASD symptom severity but positively with adaptive communication skills. Overall, we identified six intellectual profiles according to verbal and reasoning skills. These findings highlight the relevance of WISC‐V assessment for children with ASD without an IDD to individualize intervention, especially remediation. Lay Summary: This study examined WISC‐V intellectual functioning in 121 children with autism spectrum disorder (ASD) without an intellectual developmental disorder (IDD). We found their intellectual functioning to be within the average, as was that of their peers with typical development (TD), and their verbal and reasoning skills were the most discriminant. In addition, the better their intellectual functioning was, the better their adaptive communication skills and the less severe their ASD symptoms. These findings highlight the relevance of WISC‐V assessment in ASD to individualize early psychological remediation. Autism Res 2021, 14: 997–1006 . © 2020 International Society for Autism Research, Wiley Periodicals, LLC